2000
DOI: 10.1159/000007755
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Composition of Common Bile Duct Stones in Relation to Duodenal Diverticula, Gastric Resection, Cholecystectomy and Infection

Abstract: Background: Common bile duct stones represent a clinical problem often involving severe infection, cholangitis and cholestasis. Stasis and infection are thought to play a part in the pathogenesis of choledocholithiasis. Investigations on the etiology of common bile duct stones are, however, scarce because of the difficult access to common bile duct stones and bile. In a clinical series of common bile duct stones, we studied the gross appearance of stones extracted endoscopically from the common bile duct and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Research conducted on CBD stones may offer an explanation. CBD stones prevent the flow of bile into the duodenum, leading to bile stasis which has been shown to cause bacterial growth [22] . As with a CBD stone, a tumour at the head of the pancreas can also cause bile duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted on CBD stones may offer an explanation. CBD stones prevent the flow of bile into the duodenum, leading to bile stasis which has been shown to cause bacterial growth [22] . As with a CBD stone, a tumour at the head of the pancreas can also cause bile duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with diagnosed choledocholithiasis have shown elevated primary/secondary (P/S) ratios compared to pancreatic neoplasms and elevated conjugated/unconjugated (C/U) ratios of BSs when compared to benign strictures as shown in Figure 3 B,C. Blockage resulting from the gallstone formation inhibits the flow of the BSs from the gallbladder to the small intestine leading to dysbiosis and, therefore, a reduction in BSH [ 58 , 59 , 60 ]. Depletion of BSH leads to suppression of the deconjugation process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an alteration in the conjugation level and an obstruction-induced reduction of BS concentration in the small intestine may change the BS synthesis via action of FXR and promote excessive BA synthesis. Imbalance in the BA composition can be caused by a number of factors, e.g., 1. altered synthesis due to FXR promotion or inhibition [ 47 , 56 ]; 2. change in the function of BAAT; 3. change in the function of the BA transporters [ 57 ]; 4. change in the external concentration of the BS due to a blockage [ 58 , 59 , 60 ]; 5. changed function of BSH [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative explanation stems from the research on common bile duct stones. Sandstad et al showed that stones in the common bile duct could obstruct the bile flow into the duodenum, resulting in bile stasis associated with the growth of bacteria [107]. In addition, bile duct obstruction can also result from pancreatic head tumours [102].…”
Section: Bile Acid Levels Are Dysregulated In Pancreatic Cancermentioning
confidence: 99%